Bioleaching Test of Polymetallic Nodule Samples from the IOM Exploration Area - Štyriaková, Darina; Štyriaková, Iveta; Šuba, Jaroslav; Baláž, Peter; Abramowski, Tomasz (Minerals (Basel), 2022)
The Interoceanmetal Joint Organization’s (IOM) exploration license is granted in the area located within the Clarion–Clipperton Zone of the Eastern Central Pacific. All activities related to exploration of minerals in this area are beyond the limits of national jurisdiction and come under the provision of the United Nations Convention on the Law of the Sea and related regulations. The geological survey, which was the subject of the exploration, focused on the polymetallic nodule deposits. Other activities covered the tests of nodule processing, including alternative methods of metal extraction. This article describes the methodology of the bioleaching process and provides a summary of the initial results of the bioleaching test, applied to the samples of polymetallic nodules taken from the H22 exploration block of the IOM exploration area. The bioleaching efficiency under different pulp density conditions was studied. The enrichment of heterotrophic Mn-reducing microorganisms was prepared as the leaching medium. Bioleaching of the samples took place with different sample weights in order to determine the maximum possible extraction yield and the highest concentration of elements obtained in the leachate. During the bioleaching, the media were also exchanged to achieve maximum polymetallic nodule decomposition with regular addition of nutrients for heterotrophic Mn-reducing bacteria. The bioleaching efficiency of the polymetallic nodules increased to 100% (without Cu) when the pulp density was reduced to 0.1% (w/v). The discontinuous bioleaching and washing process recovered 55% Mn, 36% Ni, 15% Co, 27% Zn, and 38% Cu when the pulp density was increased to 10% (w/v). To achieve total Mn, Cu, Zn, Co, and Ni recovery from the polymetallic nodules, an intermittent bioleaching with about 25 changes of 60% of the medium was required when the pulp density was increased to 10% (w/v). Bioleaching has the potential to be used as an environmentally friendly alternative to other commonly used options for leaching and processing.